The Influence of Service Quality on Customer Loyalty with Satisfaction as a Mediating Variable - Sustiyatik, Enni; Jauhari, Tontowi (Universitas Hang Tuah, 2025)
This study aims to determine the effect of service quality on customer loyalty, the effect of service quality on customer satisfaction, the effect of customer satisfaction on customer loyalty and the effect of service quality on customer loyalty through customer satisfaction at Bank Jatim Trenggalek Branch. The effect you want to know is the direct effect. This type of research is quantitative. This study used a sample of 100 respondents. Sampling using convenience simple random sampling, namely taking sample members from the population is done randomly. The software used in this study is SmartPLS and carried out three stages of Outer Model, Inner Model and hypothesis testing. From the results of this test it can be concluded that service quality has a direct and positive influence on customer loyalty, service quality has a direct positive effect on customer satisfaction, customer satisfaction has a direct positive effect on customer loyalty and customer satisfaction can be said to be a variable partial mediation.